Development of a patient‐specific bone analog for the biomechanical evaluation of custom implants. Issue 1 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – The aim of this study is to describe an improved experimental substrate for the mechanical testing of patient‐specific implants fabricated using direct metal additive manufacturing processes. This method reduces variability and sample size requirements and addresses the importance of geometry at the bone/implant interface.Design/methodology/approach – Short‐fiber glass/resin materials for cortical bone and polyurethane foam materials for cancellous bone were evaluated using standard tensile coupons. A method for fabricating bone analogs with patient‐specific geometries using rapid tooling is presented. Bone analogs of a canine radius were fabricated and compared to cadaveric specimens in several biomechanical tests as validation.Findings – The analog materials exhibit a tensile modulus that falls within the range of expected values for cortical and cancellous bone. The tensile properties of the cortical bone analog vary with fiber loading. The canine radius models exhibited similar mechanical properties to the cadaveric specimens with a reduced variability.Research limitations/implications – Additional replications involving different bone geometries, types of bone and/or implants are required for a full validation. Further, the materials used here are only intended to mimic the mechanical properties of bone on a macro scale within a relatively narrow range. These analog models have not been shown to address the complex microscopic or viscoelastic behavior of bone in the present study.Originality/value – Scientific data on the formulation and fabrication of bone analogs are absent from the literature. The literature also lacks an experimental platform that matches patient‐specific implant/bone geometries at the bone implant interface.